Complex Admixture Preceded and Followed the Extinction of Wisent in the Wild. (21st December 2016) - Węcek, Karolina; Hartmann, Stefanie; Paijmans, Johanna L. A.; Taron, Ulrike; Xenikoudakis, Georgios; Cahill, James A.; Heintzman, Peter D.; Shapiro, Beth; Baryshnikov, Gennady; Bunevich, Aleksei N.; Crees, Jennifer J.; Dobosz, Roland; et al.
Abstract : Retracing complex population processes that precede extreme bottlenecks may be impossible using data from living individuals. The wisent ( Bison bonasus ), Europe's largest terrestrial mammal, exemplifies such a population history, having gone extinct in the wild but subsequently restored by captive breeding efforts. Using low coverage genomic data from modern and historical individuals, we investigate population processes occurring before and after this extinction. Analysis of aligned genomes supports the division of wisent into two previously recognized subspecies, but almost half of the genomic alignment contradicts this population history as a result of incomplete lineage sorting and admixture. Admixture between subspecies populations occurred prior to extinction and subsequently during the captive breeding program. Admixture with the Bos cattle lineage is also widespread but results from ancient events rather than recent hybridization with domestics. Our study demonstrates the huge potential of historical genomes for both studying evolutionary histories and for guiding conservation strategies.